2013
DOI: 10.3892/ijo.2013.1825
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type p53 suppresses the epithelial-mesenchymal transition and stemness in PC-3 prostate cancer cells by modulating miR-145

Abstract: The principal problem arising from prostate cancer (PCa) is its propensity to metastasize to bone and the mechanism(s) need to be further elucidated. The tumor suppressor p53 plays an important role in regulating the epithelial-mesenchymal transition (EMT) and cancer cell stemness, which have been proposed to play critical roles in cancer metastasis. MiR-145, a direct target of p53, represses bone metastasis of PCa and is involved in regulating EMT and cancer cell stemness. However, it is unknown whether wild‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 44 publications
3
104
0
Order By: Relevance
“…Our observation was closely consistent with a recently published report demonstrating that UCA1 promoted bladder cancer cell migration and invasion by the hsa-mir145-ZEB1/2-FSCN1 pathway (24). Similar to miR-143, miR-145 was also reported to be a tumor suppressive gene and a negative regulator of EMT (47)(48)(49). Thus, UCA1 might function as an oncogene by sponging EMT-related miRNAs.…”
Section: Discussionsupporting
confidence: 81%
“…Our observation was closely consistent with a recently published report demonstrating that UCA1 promoted bladder cancer cell migration and invasion by the hsa-mir145-ZEB1/2-FSCN1 pathway (24). Similar to miR-143, miR-145 was also reported to be a tumor suppressive gene and a negative regulator of EMT (47)(48)(49). Thus, UCA1 might function as an oncogene by sponging EMT-related miRNAs.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, Sachdeva and colleagues showed that p53 directly binds the promoter of miR145 at the p53 response element region (48). p53 was shown to suppress EMT and TICs properties by upregulating miR145 (49). These data suggest a possible mechanism that curcumin, by inducing the expression of p53, could increase the expression of miR145 in HNC-TICs.…”
Section: Cd44mentioning
confidence: 91%
“…Our data are consistent with previous studies showing that PI3K/Akt inhibitor or resveratrol treatment inhibits p-Akt and induces miR-145. Although several transcription factors, such as Foxo and p53, have been implicated in the regulation of miR-145, the silencing of miR-145 in many cancers is not clearly understood (Gan et al 2010, Ren et al 2013. The specific inhibition of the PI3K/Akt pathway has been recently reported to lead to upregulation of miR-145 in a p53-dependent manner (Sachdeva et al 2009).…”
Section: Discussionmentioning
confidence: 99%